Pengajaran Entrepreneurship dengan Metode NLP dan Pendekatan Eksplorasi di Universitas Bina Nusantara - Hutomo, Karyana (Binus Business Review, 2010)
Center for Entrepreneurship (CFE) has made the Entrepreneurship course (2 credits) to be compulsory subjects for all majors at Bina Nusantara University since 2004. In this course students are taught practical concepts in business. Teaching methods applied is by using a coaching model. With the above methodology, there are some results from those activities which affect the output of the work in diverse, where some activity is evident from the observation that results in some groups, forms of activity is still regarded by students as more than just a class assignment and therefore a burden. But in some groups, forms of activities are carried out with enthusiasm. In some groups also type of activities are not well responded either by the team in their group.Â